Lacidipine Ameliorates the Endothelial Senescence and Inflammatory Injury Through CXCR7/P38/C/EBP-β Signaling Pathway - Liu, Xing; Huang, Zhuoshan; Zhang, Yuanyuan; Shui, Xing; Liu, Fanmao; Wu, Zhen; Xu, Shiyue (Frontiers in Cardiovascular Medicine, 2021)
Background: Lacidipine, a third-generation calcium channel blocker, exerts beneficial effects on the endothelium of hypertensive patients in addition to blood pressure lowering. However, the detailed mechanism underlying Lacidipine-related endothelial protection is still elusive. Methods: Sixteen spontaneous hypertensive rats (SHRs) were randomly divided into two groups: Lacidipine-treated SHR group and saline-treated control group. Tail systolic blood pressure was monitored for four consecutive weeks. Endothelial cells (ECs) were pretreated with Lacidipine prior to being stimulated with H2O2, bleomycin, or Lipopolysaccharides (LPS) in vitro. Then, cell activity, migration, and senescence were measured by Cell Counting Kit-8 assay, transwell assay, and β-galactosidase staining, respectively. The fluorescent probe 2′, 7′-dichlorofluorescein diacetate (DCFH-DA) was used to assess the intracellular reactive oxygen species (ROS). Related protein expression was detected by Western blotting and immunofluorescence. Results: Our data showed that Lacidipine treatment lowered the blood pressure of SHRs accompanied by the elevation of CXCR7 expression and suppression of P38 and CCAAT/enhancer-binding protein beta (C/EBP-β) compared with the control group. In vitro experiments further demonstrated that Lacidipine increased the cell viability and function of ECs under oxidative stress, cell senescence, and inflammatory activation via the CXCR7/P38/signaling pathway. Conclusions: Our results suggested that Lacidipine plays a protective role in EC senescence, oxidative stress, and inflammatory injury through the regulation of CXCR7/P38/C/EBP-β signaling pathway.